2020
DOI: 10.9734/sajrm/2019/v5i430136
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Associated with the Fermentation of Gari Fortified with Sprouted Mung Beans Flour

Abstract: Gari’ is consumed regularly by large populations of Nigeria, therefore, it is an excellent means of improving the diet of people through fortification with nutritionally rich foods hence, this study aim to produce ‘Gari’ by co-fermenting cassava mash and sprouted mung bean flour in different ratios in order to assess the effect on the nutritional composition as compared to a standard produced without sprouted mungbeans (SMF) flour fortification. In different ratios, composites of cassava mash (CM) and the spro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Such as Bacillus subtilis, Klebsiella sp, Candida tropicalis, Candida krusei some Lactobacillus plantarum and Leuconostoc plantarum have been identified at the pH of 6.3+0.2 to 4.0+0.3 [38]. He also reported that Bacillus subtilis, and Klebsiella sp contribute to the rotting and softening of the soaked fleshy cassava tubers [7]. The soft tuber is mashed manually by crushing, the wooden fiber removed, the mash is sieved with a 0.2 mm sieve which separates the flour from the coarse fiber particles to form the fufu.…”
Section: Production Of Fermented Cassava Flour (Lafun/fufu)mentioning
confidence: 97%
See 1 more Smart Citation
“…Such as Bacillus subtilis, Klebsiella sp, Candida tropicalis, Candida krusei some Lactobacillus plantarum and Leuconostoc plantarum have been identified at the pH of 6.3+0.2 to 4.0+0.3 [38]. He also reported that Bacillus subtilis, and Klebsiella sp contribute to the rotting and softening of the soaked fleshy cassava tubers [7]. The soft tuber is mashed manually by crushing, the wooden fiber removed, the mash is sieved with a 0.2 mm sieve which separates the flour from the coarse fiber particles to form the fufu.…”
Section: Production Of Fermented Cassava Flour (Lafun/fufu)mentioning
confidence: 97%
“…Some microorganisms have been identified to help in the fermentation process of cassava flex. Such organisms include Lysinibacillus spp, Proteus spp, Pediococcus spp, Lactobacillus plantarum, Staphylococcus spp, and Bacillus spp were confirmed to be Lysinibacillus alkalisoli , Proteus mirabilis, Pediococcus acidilactici, Lactobacillus plantarum, Staphylococcus aureus, Bacillus subtilis and Bacillus cereus while the fungi isolate Penicillium spp, Diutina spp, Rhizopus stolonifer, Trichoderma spp and Saccharomyces cerevisiae were confirmed to be Penicillium sclerotiorum, Diutina catenulata, Rhizopus [7].…”
Section: Production Of Cassava As Flex (Called Garri)mentioning
confidence: 98%